Phylogenetic studies of babblers (Family : Timaliidae) using cytochrome oxidase I (COI) mtdna gene - Hasdiyana, Hussen (Universiti Malaysia Sarawak (UNIMAS), 2005)
Phylogenetic relationships of selected babbler species (Passerifomes: Timaliidae) were investigated using mitochondrial DNA (mtDNA) sequence data, the cytochrome oxidase I (COl). An approximately 650-700 base pair polymerase chain reaction product of the COl gene was amplified from mitochondrial DNA. Ten blood samples were obtained from two different places, namely lambusan (Bau) and Maludam National Park (Sri Aman). Phylogenetic tree inferred using Neighbor-joining (Nl) and Maximum Parsimony (MP) methods. Phlylogenetic tree shows that the babbler species evolved into two major clades. The first clade consisted of species from genus Macronolls and Stachyris and another clade formed by the species from genus Trichastoma. The advantage of using the COl as a specific genetic marker, we can differentiate two individuals within the same species.